(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2008)
New data concerning paleorelief of the Selavmastara River watershed (South-Western and Southern versants of Aragats Massif). Relationships between paleo and recent watersheds, as well as distribution of ground water flow have been discovered. Following directions of ground water flow are singled out: Haykadzor–Souser–Arteni, Haykadzor–Bagravan–Arteni, Areg–Talin, Shgharshik–Ashnak and Davtashen–V. Bazmaberd. According to general water-balance calculations the natural ground water flow of the Selavmastara watershed is estimated up to 4.33 m3/day, out of which the concentrated flow is about 2.4–2.9 m3/day.